Electricity costs and tariffs : a general study - United Nations (New York: United Nations, 1972)
This study covers not only the subject of tariff formulation, but also the interrelated questions arising form the institution of costing systems appropriate to the electricity supply industry. The report is not intended to be an exhaustive study of the subject, concerning which several highly sophisticated text-books are available, but it is hoped that the general information and examples contained therein will constitute a practical guide from which effective tariffs may be formulated for use in developing countries.
"United Nations publication. Sales no.: E.72.II.A.5."
ne 9/05/2018
Loans
Keywords: Electric utilities; Electricity tarriffs